Joint inversion of earthquake-based horizontal-to-vertical spectral ratio and phase velocity dispersion: Applications to Garner Valley - Mianshui, Rong; Li-Yun, Fu; Francisco José, Sánchez-Sesma; Weijia, Sun (Frontiers in Earth Science, 2022)
Joint inversion of horizontal-to-vertical spectral ratios (HVSRs) and dispersion curves (DCs) from seismic noise recordings has been extensively used to overcome the lack of inversion uniqueness in the noise-based HVSR (NHV) or DC inversions alone. Earthquake recordings contain information about the structural properties of sedimentary layers and provide body-wave data complementary to seismic noise recordings to estimate site velocity structures, particularly in the high-frequency band. We propose a joint inversion of the Rayleigh wave DC obtained from array measurements and earthquake-based HVSR (EHV). The EHV is derived from earthquake motions rather than from microtremors based on the diffuse-field theory of plane waves. We investigated the complementarity of EHV and surface-wave DC in the joint inversion through sensitivity analyses. The DC is sensitive to bedrock shear-wave velocities in the low-frequency range and is supplemented to some degree by the EHV in the high-frequency range. The EHV is more sensitive to sediment thicknesses almost over the entire frequency range. The joint inversion is implemented by a hybrid global optimization scheme that combines genetic algorithm (GA) and simulated annealing (SA) to avoid premature convergence in the GA. The sensitivity of inversion parameters was tested to demonstrate that the P- and S-wave velocities and thicknesses of soil layers are the dominant parameters influencing EHV and DC responses. The proposed method was validated by using synthetic models to compare the joint inversion with EHV or DC inversions alone. The joint inversion was applied to the Garner Valley Downhole Array (GVDA) data for identifying the velocity structures of the site based on earthquake and noise observations. The inversion results for the P- and S-wave velocities and thicknesses of soil layers strongly suggest that the joint inversion is an efficient method to estimate site velocity structures.